Expertise and the PhD: Between depth and a flat place. (29th August 2018) - Barnacle, Robyn; Schmidt, Christine; Cuthbert, Denise
Abstract: Expertise is under sustained interrogation. We see it in so‐called edu‐scepticism and pessimism about graduates' apparently diminishing employment prospects, challenges to the role of Higher Education institutions as arbiters of knowledge and post‐truth rhetoric more broadly. This paper examines how the PhD is being discursively positioned in this context. We ask what these changing conceptions of expertise, education and work mean for how PhD‐level expertise is understood. Drawing on a range of sources, from the scholarly to the wider media, we draw together five exemplar models of expertise to expose the transforming ratio between generalist, transferable skills and specialist knowledge. The evident diminution of specialisation raises numerous issues for the PhD as it is increasingly called upon to serve multiple and potentially contradictory needs: an innovation society on the one hand and the discipline on the other. Reconciling the tension between depth and breadth is an important issue for a degree whose hallmark is—or at least has been—depth.